Physiotherapy First Aid Training for Injured Athletes in the Field - Ummy A’isyah Nurhayati; Nabilla Aulia Cahyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sports injury is a condition of damage that occurs to the muscular and skeletal systems of the body during exercise due to an accident. Some cases of injury are often ignored by athletes and assume that the injury will recover by itself, even though if the injury is not treated properly it can lead to more serious injuries and impact on the athlete's performance. Physiotherapy is a health professions that can provide assistance to injured athletes. The lack of knowledge about the handling of injuries in athletes often has an impact on the occurrence of repetitive injuries. The aim is to provide knowledge to coaches and athletes about the types of injuries, the level of injury (onset), how to reduce the risk of further injury or repetitive injury and how to overcome injuries in the field.